Determinants of atrial bipolar voltage: Inter electrode distance and wavefront angle. (1st November 2018) - Beheshti, Mohammadali; Magtibay, Karl; Massé, Stéphane; Porta-Sanchez, Andreu; Haldar, Shouvik; Bhaskaran, Abhishek; Nayyar, Sachin; Glover, Benedict; Deno, D. Curtis; Vigmond, Edward J.; Nanthakumar, Kumaraswamy
Abstract: Background: Local bipolar electrogram (EGM) peak-to-peak voltage (Vpp) is currently used to characterise mapped myocardial substrate. However, how interelectrode distance and angle of wavefront incidence affect bipolar, Vpp values, in the current era of multi-electrode mapping is unknown. Objectives: To elucidate the effects of tissue and electrode geometry on bipolar Vpp measurements, when mapping healthy versus diseased atrial regions. Methods: A bidomain model of human atrial tissue was used to quantify the influence on Vpp values of various electrode configurations in healthy tissue, and tissue containing an unexcitable region. The orientation angle and interelectrode spacing of a surface bipole, and thickness and depth of the unexcitable core were serially varied. Results were validated with data obtained from isolated porcine hearts. Results: In healthy tissue, bipolar Vpp values increased with increasing interelectrode spacing and plateaued beyond a spacing of approximately 4 mm. The bipolar Vpp values in healthy tissue were relatively less sensitive to wavefront orientation angle with large interelectrode spacing. In diseased tissue, on the contrary, with increasing interelectrode spacing, bipolar Vpp values increased linearly without a plateau and were more sensitive to orientation angle. The bipolar Vpp values decreased with increasing thickness of the scar, with larger relative decrease in small bipoles than larger ones. Bipolar Vpp values increased with a progressively intramural location of fixed-size scar and became less distinguishable from healthy tissue especially for smaller interelectrode spacings. Conclusions: The scalable relationship established for interelectrode distances favour an electric-field-based assessment as opposed to traditional Vpp values as a tool for physiologically relevant measurement for mapping catheters with interelectrode spacing up to 4 mm. This will allow for universal assessment of myocardial health across catheters with varied spacing. Highlights: Bipolar voltages are based on electric field measurements of the myocardium. Interelectrode distance influences bipolar voltage values. Wavefront angle to an electrode affects bipolar voltage values. Bipolar voltage values can be scaled with electrode distance less than 4 mm. Electric-field-based measurement could be an alternative to bipolar voltage.